The Author's Contributions to Echocardiography Literature (Part I-1978-1990) - P. Syamasundar Rao (MDPI AG, 2020)
The author has undertaken multiple echocardiographic studies during his academic career; most of these were published in peer-reviewed journals. These studies include an evaluation of the role of echocardiography in the estimation of left-to-right shunt in isolated ventricular septal defects, an examination of the utility of contrast echocardiography in the diagnosis of anomalous connection of the right superior vena cava to the left atrium, a description of pitfalls in M-mode echocardiographic assessment of the aortic root in left ventricular hypoplasia syndromes, reviews of echocardiographic evaluation of left ventricular function, study of the role of contrast echocardiography in the evaluation of hypoxemia following open heart surgery, a quantification of left ventricular muscle mass by m-mode echocardiography in children, an examination of race and sex related differences in echocardiographic measurements in children, study of cardiac size and function in patients with sickle cell disease, an examination of afterload reduction in the management of primary myocardial disease, study of the utility of echo-Doppler studies in the evaluation of the results of balloon pulmonary valvuloplasty, study of the usefulness of Doppler in the prediction of pressure gradients in valvar pulmonary stenosis, a review of Doppler echocardiography in noninvasive diagnoses of heart disease, echo-Doppler studies of the evaluation of the results of balloon angioplasty of aortic coarctation, study of the value of Doppler in the prediction of pressure gradients across coarctation of the aorta, and a characterization of foramen ovale and transatrial Doppler velocity patterns in the normal fetus.